2023
DOI: 10.1021/acscatal.2c05590
|View full text |Cite
|
Sign up to set email alerts
|

Operando Studies of Electrochemical Denitrogenation and Its Mitigation of N-Doped Carbon Catalysts in Alkaline Media

Abstract: N-doped carbons (NCs) have excellent electrocatalytic performance in oxygen reduction reaction, particularly in alkaline conditions, showing great promise of replacing commercial Pt/C catalysts in fuel cells and metal−air batteries. However, NCs are vulnerable when biased at high potentials, which suffer from denitrogenation and carbon corrosion. Such material degradation drastically undermines the activity, yet its dynamic evolution in response to the applied potentials is challenging to examine experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…The nitrogen content was decreased from 4 to 2.1% after ADT due to corrosion and denitrogenation. 80,81 Whereas the surface cobalt content detected was less for both before and after ADT since it is trapped inside the carbon shell evident from the TEM image. Hence, we can infer that the Co(0) phase contributed more toward ORR since only negligible ORR activity loss was observed after ADT, though the surface nitrogen content was decreased.…”
Section: Electrochemical Kinetics Analysismentioning
confidence: 98%
“…The nitrogen content was decreased from 4 to 2.1% after ADT due to corrosion and denitrogenation. 80,81 Whereas the surface cobalt content detected was less for both before and after ADT since it is trapped inside the carbon shell evident from the TEM image. Hence, we can infer that the Co(0) phase contributed more toward ORR since only negligible ORR activity loss was observed after ADT, though the surface nitrogen content was decreased.…”
Section: Electrochemical Kinetics Analysismentioning
confidence: 98%
“…45 Additionally, the oxidation of N pyridinic is thermodynamically more preferable than that of C pyridinic (C bonded with N pyridinic ). 24 So far, the oxidations are independent of the presence of O 2 as the oxidant is water. However, in O 2 , in addition to being oxidized to NO x at 1.5 V RHE (see Scheme 2D-ii), the N pyridinic on the armchair edge may also be converted into N pyridinic-COH/pyridonic during the step at 0.93 V RHE , where slow ORR occurs (see Scheme 2D-iii).…”
Section: Additional N Species After the Degradationmentioning
confidence: 99%
“…Compared to the degradation during regular fuel cell operation, the degradation during start–stop events is more harmful to the Fe–N–C catalysts. , During start–stop events, the C matrix and the N species may also undergo electrochemical oxidation, known as carbon corrosion (Reaction and ) and denitrogenation (Reaction ), respectively. Their onset potentials (defined as potentials at which CO x and NO x products are experimentally measured) are all reported to be around 1.2 V RHE at 25 °C. , Thus, they both occur during start–stop events, when the Fe–N–C electrodes experience potentials up to 1.5 V RHE . Note that the free energy barrier (Δ E b ) of denitrogenation of N-doped C (Reaction ) varies with the type of N species undergoing oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 We and others also reported that different noble metal species can speed up the oxidation of the adjacent carbon atoms. 20,21 For example, Choi et al 22 compared the electrochemical corrosion behaviors of different carbon substrates and found that the presence of Pt nanoparticles promotes carbon corrosion to yield CO in alkaline electrolytes. The dominant partial oxidation of carbon to CO is also observed in acidic environments.…”
Section: Introductionmentioning
confidence: 99%